Unusual gastroduodenal intussusception secondary to a gastrointestinal stromal tumor of the gastric fundus. (2016) - Komatsubara, Toshihide; Zuiki, Toru; Lefor, Alan Kawarai; Hirota, Norio; Oki, Jun
Highlights: Gastroduodenal intussusception caused by a tumor of the fundus is a rare entity. GISTs, which cause gastroduodenal intussusception, are symptomatic and need surgery. If endoscopic reduction is not possible and the mass is too large for laparoscopic resection, open surgery can be performed. Abstract: Introduction: Intussusception is uncommon in the proximal gastrointestinal tract. Although there are a few case reports of gastroduodenal intussusception, it is extremely rare that a tumor located in the gastric fundus causes gastroduodenal intussusception. We report a patient with gastroduodenal intussusception secondary to a gastrointestinal stromal tumor (GIST) in the gastric fundus. Presentation of case: A 90-year-old woman was admitted with appetite loss and recurrent vomiting. Esophagogastroduodenoscopy showed cord-like mucosa of the gastric fundus pulled into the duodenal bulb. Abdominal computed tomography scan showed a well demarcated round tumor in the duodenum. The patient underwent a laparotomy, since endoscopic reduction of the tumor was not successful. The tumor was reduced by gently reducing the mass. A small incision was made in the anterior wall of the stomach, and the tumor was resected. The pathological findings of the tumor showed GIST. The postoperative course was uneventful. Discussion: There were only eight patients in the world literature, including the present case, reported with gastroduodenal intussusception secondary to a GIST in the gastric fundus. All patients presented with ball valve syndrome, known as a cause of acute abdomen. Three tumors were reducible preoperatively. Five of the eight tumors were resected with an intra-gastric open surgical approach. Conclusion: We report a patient with gastroduodenal intussusception caused by a rare GIST in the gastric fundus, which needed resection.